Sociological and Anthropological Studies of Stunting Families in Malang Regency - I Dewa Nyoman Supariasa; Ibnu Fajar; Sugeng Iwan Setyobudi; Khairuddin Khairuddin (Health Notions, 2023)
Stunting is a growth disorder in toddlers and is often found in children aged less than 24 months. Basic Health Research stated that the national prevalence of stunting under five children in 2013 was 37.2%, which means there was an increase compared to 2010 (35.6%) and 2007 (36.8%). The prevalence of stunting under five in Malang Regency tends to increase in the first 3 years and decrease in the last 2 years during the 2012-2016 period. The highest prevalence was in 2014 at 30.6% and the lowest prevalence occurred in 2016 at 22.9%. The purpose of this study was to analyze the sociological and anthropological factors of stunting families in Malang Regency. This study employed a qualitative approach and design to examine the issue of stunting in three villages within Malang Regency. The study focused on families with stunted children as the primary participants. A total of 33 families were selected as samples, with 11 families chosen from each village. In addition to the families, the study also conducted Focus Group Discussions (FGDs) with various stakeholders. The participants in the FGDs included village heads, cadres, teachers, religious leaders, and members of the village's women's organization. Each village had five participants, resulting in a total of 15 participants across the three villages. The collected data were analyzed using a descriptive approach, which allowed for a comprehensive understanding of the research findings. Among the pregnant women surveyed, 78.8% followed a satisfactory pattern of consuming food three times a day. However, only 24.2% demonstrated a balanced diet during pregnancy, including staple foods, vegetables, animal and vegetable side dishes, fruits, and milk. Some pregnant women adhered to food taboos based on their beliefs, avoiding sea fish, kelotok fish, petai, pineapple, and durian. Breastfeeding was practiced by 93.9% of the surveyed households. However, 60.61% of toddlers showed a severe deficit in energy intake, while 69.7% consumed an excessive amount of protein. Fat intake was reported by 39.39% of respondents, and carbohydrate intake by 87.88%. In terms of knowledge levels, 15.1% of respondents exhibited good knowledge, 30.3% had moderate knowledge, and 45.5% had lower levels of knowledge. Regarding sanitation, 81.82% of households had access to latrine services, while 18.18% did not. Drinking water sources varied, with 18.82% relying on boiled water and 18.18% using bottled water. However, cleanliness within most of the respondents' residences was still lacking. Several anthropological and sociological factors play a significant role in the occurrence of stunting in toddlers, which include factors of maternal eating habits during pregnancy, dietary restrictions, the mother's knowledge of nutrition and feeding practices, and poor household sanitation. These factors contribute to the prevalence of stunting in young children. Keywords: stunting; sociology; anthropology